A study on in-vitro behaviour of stainless steel 316L subjected to rotational magnetorheological abrasive flow finishing process. (23rd September 2022) - Karthikeyan, S; Mohan, B; Kathiresan, S; Anbuchezhiyan, G
Abstract: In Rotational Magnetorheological Abrasive Flow Finishing (R-MRAFF) process, Magnetic Field Intensity (MFI) is the primary factor for the formation of ferrous chains which is responsible for finishing. Changing the pole distance between magnets to achieve a difference in MFI values will alter the strength of the ferrous chains. In this study, three different MFI values such as 0.34, 0.36, and 0.40 Tesla were chosen for finishing on Stainless Steel 316L (SS 316L). Surface wettability, bio-corrosion, and hemocompatibility studies were conducted to investigate the in-vitro behavior of SS 316L. The wettability of the implants changed from hydrophobic (100.92°) to hydrophilic (83.452°) surface as the MFI value increased. Bio-corrosion studies revealed improved corrosion resistance for R-MRAFF process finished samples, with the corrosion rate reduced from 3.693 to 0.967 μ m year −1 . Hemocompatibility of SS 316L was improved with reduced platelet adhesion when compared to the pristine sample.